Marketing Management of Education Services In Increasing the Number of Students In Primary Education Institutions - Halimatuzzahrah, Halimatuzzahrah; Zulfahmi Akbar, Muhammad (LP2M IAI NURUL HAKIM, 2024)
Marketing Management of Education Services In Increasing the Number of Students In Primary Education Institutions Halimatuzzahrah1M.Zulfahmi Akbar2 Institut Agama Islam Nurul Hakim Lombok Barat Email: zahrah211096@gmail.com1akbarfahmi636@gmail.com Abstract This study investigates the role of educational services marketing management strategies in increasing the number of students at MI Nurul Hikmah Lantan. Through a descriptive qualitative approach, data were obtained through interviews with various related parties, such as managers, teachers, students, and parents. The content analysis method was used to analyze the collected data. The findings of this study indicate that MI Nurul Hikmah Lantan successfully implemented an educational services marketing management strategy by emphasizing the education services mix, namely product, price, place, process, promotion, distribution, and people. First, the school focuses on the quality of educational services by ensuring that the curriculum provided meets students' needs and meets applicable educational standards. Second, regarding promotion, MI Nurul Hikmah Lantan adopts various marketing strategies, including social media, the official website, and participation in education fairs to increase exposure and attract prospective students and parents. Third, special attention is paid to pricing and distribution by providing free tuition and conducting free programs. The effective integration of these components of the education service mix has helped MI Nurul Hikmah Lantan build a reputation and increase the number of students as an excellent educational institution that focuses on student needs. Therefore, this study provides a deep insight into the importance of educational services marketing management in increasing student enrollment and strengthening the competitive position of an educational institution. Future research can focus on further evaluation of more specific marketing strategies and their impact on student enrollment growth in other educational institutions. Keywords: Management, Marketing of Educational services, increasing the number of students